1981
DOI: 10.1007/bf00443255
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload and desferrioxamine chelation therapy in β-thalassemia intermedia

Abstract: This study on serum ferritin levels in urinary iron excretion after 12h subcutaneous infusion of desferrioxamine in 10 thalassemia intermedia patients shows that even nontransfusion-dependent patients may have positive iron balance resulting in iron overload from 5 years of age. However, the iron overload found in these patients appears to be much lower than in age matched patients with transfusion-dependent thalassemia major. Iron overload increases with advancing age, as shown by increasing serum ferritin le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 10 publications
0
35
0
1
Order By: Relevance
“…These data provide the largest set of efficacy and safety data for iron-chelation therapy in NTDT patients to date, confirming preliminary findings in small studies and case reports. 4,[8][9][10][11][12][13][14] Despite no or only sporadic transfusions in these NTDT patients, high baseline LIC and serum ferritin levels confirm significant iron burden requiring iron chelation. In patients receiving placebo treatment, LIC and serum ferritin increased by 0.38 mg Fe/g dw (95% CI, Ϫ0.59 to 1.34) and 115 ng/mL, respectively, over 1 year; only 6 (10.7%) patients required transfusions in this group during this time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data provide the largest set of efficacy and safety data for iron-chelation therapy in NTDT patients to date, confirming preliminary findings in small studies and case reports. 4,[8][9][10][11][12][13][14] Despite no or only sporadic transfusions in these NTDT patients, high baseline LIC and serum ferritin levels confirm significant iron burden requiring iron chelation. In patients receiving placebo treatment, LIC and serum ferritin increased by 0.38 mg Fe/g dw (95% CI, Ϫ0.59 to 1.34) and 115 ng/mL, respectively, over 1 year; only 6 (10.7%) patients required transfusions in this group during this time.…”
Section: Discussionmentioning
confidence: 99%
“…2 Iron overload in NTDT patients results primarily from increased intestinal iron absorption caused by ineffective erythropoiesis 3 and may develop as early as 5 years of age. 4 Iron overload usually becomes clinically relevant after 10 years, 5 making iron loads in NTDT patients in their 30s and 40s comparable to those in transfusion-dependent ␤-thalassemia patients. 3 For example, in a previous study of ␤-thalassemia major patients (mean age, 17 years), LIC was 11.1 mg Fe/g dry weight (dw), although this may reflect prior suboptimal chelation therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[92][93][94] A beneficial effect of iron chelation in reducing clinical morbidity risk in patients with NTDT is suggested by observational studies and further long-term studies in this direction are needed.…”
Section: Iron Chelation Therapymentioning
confidence: 99%
“…However, progressive iron overload still occurs due to increased gastrointestinal (GI) iron absorption. [3][4][5] Studies in thalassemic patients showed that the rate of iron uptake from the GI tract is approximately 3 to 4 times greater than normal. 6 Ferrokinetic studies revealed that 75% to 90% of the iron in donor serum, labeled with 59 Fe and injected into healthy subjects, appeared in circulating red cells within 7 to 10 days.…”
Section: Introductionmentioning
confidence: 99%